Management of a child with pulmonary arterial hypertension presenting with systemic hypertension. (17th June 2015) - Flores, Saul; Daily, Joshua; Pratap, Jayant "Nick"; Cash, Michelle C.; Hirsch, Russel
Abstract: We describe the course and management of a 12-year-old girl with severe pulmonary arterial hypertension who initially presented with severe systemic hypertension. Successful therapy included pulmonary vasodilators and an atrial septostomy, while ensuring adequate maintenance of her systemic vascular resistance to maintain cardiac output. Clear understanding of the physiology and judicious medical management in patients with severe pulmonary arterial hypertension using extreme compensatory mechanisms is vitally important.